MODEL PREDIKSI KEPATUHAN MINUM OBAT ANTIRETROVIRAL DI LAYANAN PERAWATAN DUKUNGAN PENGOBATAN KOTA BOGOR - Amalia, Karina; Purnamawati, Dewi; Ritonga, Yusniar; Endah, Tria Astika; Nurfadhilah , Nurfadhilah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Background: The significant increase in HIV and AIDS cases has made WHO targeted triple 90 by 2030. Triple 90 consists of achieving 90% of diagnosed cases, 90% of HIV cases receiving appropriate treatment and 90% of patients having their viral load depressed. Adherence to taking ARV drugs is one of the key factors to achieve this target. Objective: To create a predictive model of patient adherence to taking anti-retroviral (ARV) drugs in Bogor Care Supporting Therapy. Methods: The research design used in this study was cross sectional, conducted at the Bogor Care Supporting Therapy in July 2022. The sampling technique was random sampling and analyzed with multiple logistic regression. Results: The distribution of the level of compliance with ODHA in the CST Service in Bogor City was 82.69%. The majority of ODHA in Bogor CST services are male (80.7%), aged <40 years (81.73%), have high knowledge (78.81%), receive support from their family (78.85%), receive support from the role of health workers (71.75 %), felt that the test and treat method had a high impact on him (84.62%), only had 1 risk factor (84.72%) and had an undetected viral load (91.35%). Knowledge is able to predict adherence to taking ARV drugs in ODHA by 33.2% after being controlled by variables of age, gender, family support, role of health workers, test and treat methods, risk factors and viral load. Conclusion: ODHA with high knowledge are 25 times more likely to adhere to ARV drugs than those with low knowledge. This model is able to predict patient adherence to ARV drugs by 33.2%, the rest is predicted by other factors not examined in this study. Suggestion: In order to maximize multilevel educational programs for ODHA, maximize the test and treat method in Bogor Care Supporting Therapy and create training programs for health workers in Bogor Care Supporting Therapy